1996
DOI: 10.1155/1996/678145
|View full text |Cite
|
Sign up to set email alerts
|

A Cost‐Benefit Analysis of Prenatal Screening for Toxoplasmosis

Abstract: The objective of this study was to examine critically the validity of a toxoplasma prenatal screening program, in the context of a cost-benefit analysis, as it relates to the Canadian experience. Recently, studies have suggested that early treatment of infected infants with a combination of pyrimethamine and sulfadiazine is effective in reducing the sequelae of toxoplasmosis. It was concluded that a carefully planned screening program for detecting and treating infants infected with Toxoplasma gondii during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…No cost-benefit analysis of neonatal screening in this cohort in Massachusetts and New Hampshire have been published, but studies in Europe and Canada have performed such analyses. Sahai and Onyett 23 studied prenatal screening in Canada and reported that at incidence rates even below the current estimates in Canada at the time, the cost of screening prenatally was easily justified when compared with the cost of long-term medical, social, and educational services for the patients and their families of those affected. European studies have concluded with a similar notion.…”
Section: Discussionmentioning
confidence: 99%
“…No cost-benefit analysis of neonatal screening in this cohort in Massachusetts and New Hampshire have been published, but studies in Europe and Canada have performed such analyses. Sahai and Onyett 23 studied prenatal screening in Canada and reported that at incidence rates even below the current estimates in Canada at the time, the cost of screening prenatally was easily justified when compared with the cost of long-term medical, social, and educational services for the patients and their families of those affected. European studies have concluded with a similar notion.…”
Section: Discussionmentioning
confidence: 99%